Nanocomposites in 3D Bioprinting for Engineering Conductive and Stimuli‐Responsive Constructs Mimicking Electrically Sensitive Tissue. Issue 2 (4th December 2021) - Züger, Fabian; Marsano, Anna; Poggio, Martino; Gullo, Maurizio R.
Abstract : Rebuilding damaged or diseased tissue by means of biological additive manufacturing has recently gained lot of attention and shown very promising result. Using biofabrication techniques to mimic and replicate natural tissue as well as cell environment is a very capable way to achieve physiologically relevant conditions. Especially in electrophysiological human tissue like cardiac or neural tissue, proper signal transduction is of paramount importance for appropriate function and cell maturation as well as differentiation. Precisely, these conductive properties are challenging to engineer. However, a lot of outstanding work has been done recently. Therefore, this review focuses on additives, i.e., nanocomposites with intrinsic conductive properties, to the usually nonconductive hydrogels used in 3D‐bioprinting. Recent work on exploiting the properties of these nanocomposites, such as metal nanoparticles (NPs), carbon nanotubes (CNTs), graphene, or MXenes, to alter the nanoenvironment of the manufactured construct toward conductive tissues is presented. An overview of responsiveness to external stimuli, a second intrinsic property of such nanocomposites is provided as well. Furthermore, these materials are critically analyzed concerning their electrophysiology, i.e., cell–scaffold interaction, their biocompatibility as well as their toxicological properties. Abstract : Biofabrication techniques combined with intrinsic conductive additives, i.e., nanocomposites are a very capable way of achieving relevant physiological conditions especially in electrophysiological human tissue like cardiac and neural tissue. Due to recent outstanding work in this field, this review provides an overview of the state‐of‐the‐art research on 3D‐bioprinted conductive and stimuli responsive constructs using nanocomposites for mimicking electrically sensitive tissue.